Identifikasi Dan Analisis Potensi Sumber Daya Lokal Berbasis Masyarakat Kecamatan Tehoru Kabupaten Maluku Tengah - Roy Allan Wattimena; Dirk Berly Tehuayo; Maslan Abdin (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to identify, analyze, and formulate strategies for developing community-based local resource potential in Tehoru District, Central Maluku Regency. The study used a qualitative descriptive approach with data collection techniques through participatory observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation. Data analysis was conducted using SWOT analysis, IFAS-EFAS, Analytical Hierarchy Process (AHP), and a foresight approach. The results of the study indicate that Tehoru District has superior potential in the agriculture, fisheries, plantations, and nature tourism sectors spread across 10 villages. All villages are in Quadrant I (SO-Aggressive), which indicates that internal strengths and external opportunities are more dominant than the weaknesses and threats faced. Priority development strategies include modernizing agriculture and plantations, strengthening MSMEs based on local potential, developing nature and cultural tourism, and strengthening village economic institutions such as BUMDes and farmer groups. Foresight analysis shows that technology-based development, strengthening community capacity, and sustainable environmental management are important factors in realizing Tehoru as a community-based agro-industry and agro-tourism area in the future.